Meningkatnya Pertumbuhan Penduduk Berdampak Pada Terjadinya Alih Fungsi Lahan Hutan Di Sumatera Utara - Annisa Zahra Lubis; Asraaf Efendi Batubara; Ashabul Jannah Siregar; Auliya Ahmad Suhardi; Dini Andriani Nasution; Intan Sari Tanjung; Muhammad Rivaldi Pane; Yusrizal Yusrizal (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Along with the development of the era which is increasingly advanced, the population growth rate is increasing, resulting in the need for natural resources to meet all human needs, including land. The difficulty of finding land causes the conversion of forest land to be used for residential areas, places of business, factories, offices and so on. The purpose of this research is to find out and understand the impact of increasing population growth on the conversion of forest land in North Sumatra. This research is a qualitative research conducted using a literature study.